Catheter-Based Therapies Decrease Mortality in Patients With Intermediate and High-Risk Pulmonary Embolism: Evidence From Meta-Analysis of 65,589 Patients - Pietrasik, Arkadiusz; Gąsecka, Aleksandra; Szarpak, Łukasz; Pruc, Michał; Kopiec, Tomasz; Darocha, Szymon; Banaszkiewicz, Marta; Niewada, Maciej; Grabowski, Marcin; Kurzyna, Marcin (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter-directed therapies (CDT) are an alternative to systemic thrombolysis (ST) in pulmonary embolism (PE) patients, but the mortality benefit of CDT is unclear. Objective: We conducted a systematic review with meta-analysis to compare the efficacy and safety of CDT and ST in intermediate-high and high-risk PE. Methods: We included (P) participants, adult PE patients; (I) intervention, CDT; (C) comparison, ST; (O) outcomes, mortality, complications, in-hospital treatment and length of hospital stay; (S) study design, randomized controlled trials (RCTs) or cohort comparing CDT and ST. The primary endpoint was 30-day mortality. Secondary outcomes included treatement-related complications including bleeding, the use of hospital resources and length of hospital stay. Results: Eleven studies including 65,589 patients met the inclusion criteria. Thirty-day mortality was lower in the CDT group, compared to ST group (7.3% vs. 13.6%; odds ratio [OR]=0.51, 95% confidence interval [CI] 0.38–0.69, p<0.001). The rates of myocardial injury, cardiac arrest and stroke were lower in CDT group, compared to ST group (p<0.001 for all). The rates of any major bleeding, intercranial hemmorhage, hemoptysis and red blood cell transfusion were lower in patients treated with CDT, compared to ST (p≤0.01 for all). Extracorporeal life support was used more often in patients treated with CDT, compared to ST (0.5% vs. 0.2%, OR=2.52, 95% CI 1.88-3.39, p<0.001). The use of hospital resources and length of hospital stay were comparable in both groups. Conclusions: CDT might decrease mortality in patients with intermediate-high and high-risk PE and were associated with less complications, including major bleeding.